Identification of an unconventional E3 binding surface on the UbcH5 ∼ Ub conjugate recognized by a pathogenic bacterial E3 ligase. - Levin, Itay (National Academy of Sciences, 2010)
Gram-negative bacteria deliver a cadre of virulence factors directly into the cytoplasm of eukaryotic host cells to promote pathogenesis and/or commensalism. Recently, families of virulence proteins have been recognized that function as E3 Ubiquitin-ligases. How these bacterial ligases integrate into the ubiquitin (Ub) signaling pathways of the host and how they differ functionally from endogenous eukaryotic E3s is not known. Here we show that the bacterial E3 SspH2 from S. typhimurium selectively binds the human UbcH5 ∼ Ub conjugate recognizing regions of both UbcH5 and Ub subunits. The surface of the E2 UbcH5 involved in this interaction differs substantially from that defined for other E2/E3 complexes involving eukaryotic E3-ligases. In vitro, SspH2 directs the synthesis of K48-linked poly-Ub chains, suggesting that cellular protein targets of SspH2-catalyzed Ub transfer are destined for proteasomal destruction. Unexpectedly, we found that intermediates in SspH2-directed reactions are activated poly-Ub chains directly tethered to the UbcH5 active site (UbcH5 ∼ Ub(n)). Rapid generation of UbcH5 ∼ Ub(n) may allow for bacterially directed modification of eukaryotic target proteins with a completed poly-Ub chain, efficiently tagging host targets for destruction.